Epidemiology and surveillance of amyotrophic lateral sclerosis in two large metropolitan areas in California. Issue 3 (June 2015) - Valle, Jhaqueline; Roberts, Eric; Paulukonis, Susan; Collins, Natalie; English, Paul; Kaye, Wendy
Abstract Our objective was to provide demographic profiles and incidence estimates of amyotrophic lateral sclerosis (ALS) in two diverse California metropolitan areas: Los Angeles County (LA) and the San Francisco Bay Area (SFBA). Data were retrospectively collected from multiple sources. Case eligibility criteria included residency in SFBA or LA, and treatment for or diagnosis of ALS between 1 January 2009 and 31 December 2011. Overall incidence rates as well as age-, gender-, race- and ethnicity-specific rates were calculated. We identified 539 ALS cases in SFBA and 545 in LA; 618 were incident cases. Cases were more likely to be male and white. There were considerably more cases (p < 0.05) in LA who were foreign-born (LA, 22%; SFBA, 15%), black (LA, 10%; SFBA, 6%) or Hispanic (LA, 19%; SFBA, 10%). Conversely, the age adjusted incidence rates (per 100, 000) were higher in SFBA for whites (LA, 1.40; SFBA, 2.49) and Hispanics (LA, 0.66; SFBA, 1.57) compared with LA. General case demographics and incidence rates in these two areas were similar to published studies. However, the differences between the two areas raise questions about how factors such as geography, access to care, and referral patterns may affect case ascertainment and diagnosis.